Reference values for body composition and associations with blood pressure in Kenyan adults aged ≥50 years old - Bastawrous, M; Piernas Sanchez, C; Bastawrous, A; Oke, J; Lasserson, D; Mathenge, W; Burton, M; Jebb, S; Kuper, H (Springer Nature, 2018)
Objectives: To develop age and sex-specific centile reference curves for fat free mass (FFM) and fat mass (FM) adjusted for height in an adult Kenyan population and to investigate the association between FM, FFM and blood pressure (BP). Methods: Measures of body composition from bioimpedance analyses and BP were collected in 1,995 participants aged ≥50y in Nakuru County, Kenya. Reference curves were produced using the LMS method. Multivariable linear regression models were used to test the cross-sectional association between body composition indexes and BP. Results: The age and sex-specific reference curves for body composition (FMI and FFMI) confirm that FFMI is lower in both men and women with increasing age. FMI declines with age in women while among men the decline starts after 70 years. FFM was higher in men (47.4 ± 7.2 kg) than in women (38.8 ± 5.5 kg), while FM was lower in men (17.3 ± 8.1 kg) than in women (24.4 ± 10.2 kg). FMI, FFMI and BMI were all positively associated with systolic and diastolic BP, and after adjusting for body weight, FFMI remained positively associated with systolic BP and the FMI remained positively associated with diastolic BP. There was no evidence to suggest that FMI and FFMI were superior to measurement of BMI alone. Conclusion: These body composition reference curves provide normative data on body composition for older adults in Kenya. Further research should consider the prospective associations with health, including frailty-related outcomes.